Assessing cerebellar brain inhibition (CBI) via transcranial magnetic stimulation (TMS): A systematic review. (March 2018) - Fernandez, Lara; Major, Brendan P.; Teo, Wei-Peng; Byrne, Linda K.; Enticott, Peter G.
Highlights: Cerebellar-M1 connectivity may be assessed via a dual-coil TMS paradigm. There is some controversy surrounding the paradigm. CBI: Activating cerebellar Purkinje cells via TMS inhibits MEPs following an M1 pulse. Variability in protocol parameter choice may reduce study reliability. CBI assessment is applicable to a wide range of research questions. Abstract: The inhibitory tone that the cerebellum exerts on the primary motor cortex (M1) is known as cerebellar brain inhibition (CBI). Studies show CBI to be relevant to several motor functions, including adaptive motor learning and muscle control. CBI can be assessed noninvasively via transcranial magnetic stimulation (TMS) using a double-coil protocol. Variability in parameter choice and controversy surrounding the protocol's ability to isolate the cerebellothalamocortical pathway casts doubt over its validity in neuroscience research. This justifies a systematic review of both the protocol, and its application. The following review examines studies using the double-coil protocol to assess CBI in healthy adults. Parameters and CBI in relation to task-based studies, other non-invasive protocols, over different muscles, and in clinical samples are reviewed. Of the 1398 studies identified, 24 met selection criteria. It was found that methodological design and selection of parameters in several studies may have reduced the validity of outcomes. Further systematic testing of CBI protocols is warranted, both from a parameter and task-based perspective.